ENGLISH TEACHERS’ STRATEGIES IN TEACHING WRITING DESCRIPTIVE TEXT FOR SEVENTH GRADE OF SMPN 7 TANJUNG BALAI - Nurul Sakinah Nasution; Neni Afrida Sari Harahap (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
This study aims to analyze the teachers’ strategies in teaching writing descriptive text and to elaborate the procedures of teaching strategies used by the English teachers for seventh grade at SMPN 7 Tanjung Balai. The researcher used a qualitative descriptive method used in doing this research. This study found there were two teachers as the data. The first teacher applied three strategies, they were (1) TTW (Think – Talk –Write) strategy, (2) scaffolding strategy, and (3) guided writing strategy. While the second teacher applied three strategies as well. They were (1) P.L.E.A.S.E strategy, (2) TTW (Think – Talk –Write) strategy, and (3) guided writing strategy. In teaching the topic, there are the procedures. The procedures of each strategy applied by the English teachers were: (1) Preteaching activity: there is no suitable steps for this procedure. (2) Whilst-teaching activity: P.L.E.A.S.E Strategy, TTW (Think-Talk-Write) strategy, and guided writing strategy. And for (3) post-teaching activity: guided writing strategy.Keywords: Teacher’s strategy, Teaching procedure